2019
DOI: 10.1289/ehp3395
|View full text |Cite
|
Sign up to set email alerts
|

Daily Walking among Commuters: A Cross-Sectional Study of Associations with Residential, Work, and Regional Accessibility in Melbourne, Australia (2012–2014)

Abstract: Background:Most research on walking for transport has focused on the walkability of residential neighborhoods, overlooking the contribution of places of work/study and the ease with which destinations outside the immediate neighborhood can be accessed, referred to as regional accessibility.Objectives:We aimed to examine if local accessibility/walkability around place of work/study and regional accessibility are independently and interactively associated with walking.Methods:A sample of 4,913 adult commuters wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
(63 reference statements)
2
11
0
Order By: Relevance
“…Conversely, a positive relationship between age and TRPA was observed among only three studies, in which women of lower socio-economic status [ 34 , 41 , 47 ] reported greater TRPA levels with higher age. Twenty-four studies found there to be no significant association between age and TRPA level [ 14 , 30 , 32 , 33 , 35 , 40 , 45 , 50 , 52 54 , 58 , 59 , 62 , 67 69 , 72 , 78 , 82 , 88 , 92 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, a positive relationship between age and TRPA was observed among only three studies, in which women of lower socio-economic status [ 34 , 41 , 47 ] reported greater TRPA levels with higher age. Twenty-four studies found there to be no significant association between age and TRPA level [ 14 , 30 , 32 , 33 , 35 , 40 , 45 , 50 , 52 54 , 58 , 59 , 62 , 67 69 , 72 , 78 , 82 , 88 , 92 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles reported male participants undertaking a greater amount of TRPA than women (three assessed walking and cycling combined into a single measure of TRPA [ 29 , 66 , 67 ], two walking only [ 52 , 87 ], and four presented walking and cycling for commute separately [ 47 , 57 , 69 , 72 ]).Of these, two studies reported that men were more likely to cycle for active transport compared to women [ 57 , 69 ]. Dissimilarly, three studies found women had a higher probability of engaging in TRPA and a greater likelihood of high levels of active transport [ 46 , 53 , 74 ]; 21 studies observed no association to be present [ 14 , 30 , 32 35 , 40 , 45 , 50 , 54 , 56 , 58 , 59 , 63 , 70 , 71 , 75 , 78 , 92 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decades, when transportation dynamics have been experiencing several transformations, walking has been systematically promoted as a cheap (Audrey et al, 2014), sustainable (Grant, Machaczek, Pollard & Allmark) and healthy (Hanson and Jones, 2015) means for performing short and mid-length tripsor parts of them -for daily commuting (Barr et al, 2019;Oja et al, 1998). Indeed, many organizational and educational stakeholders have been recently promoting "active commuting" (i.e., using non-motorized transportation means such as walking or cycling) for commuting trips, as a way of encouraging their employees/students to improve their lifestyle and health outcomes (Barranco-Ruiz et al, 2019;Page and Nilsson, 2017;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%